Outcomes Following Primary Excision of Ocular Surface Squamous Neoplasia at a Tertiary Eye Care Centre in the Midwestern Region of Nepal - Bhandari, Ipsa; Sapkota, Jyoti; Subedi, Santosh; Karakheti, Arati (Nepalese Journal of Ophthalmology, 2025)
Introduction: Ocular surface squamous neoplasia (OSSN) includes variety of tumours ranging from mild epithelial dysplasia to invasive squamous cell carcinoma. Squamous lesions of conjunctiva and cornea are important clinical entities due to potential risk of significant ocular and even systemic morbidity and mortality. Objective: To determine demographic profile, clinical presentation, histopathological features, and surgical outcomes of OSSN. Methodology: This hospital-based, retrospective, observational study was conducted from 2021 July to 2025 April after ethical approval among all consecutive patients diagnosed with biopsy-proven OSSN at Rapti Eye Hospital. Main outcomes examined included demographic profile, clinical presentation, histopathological features, and surgical results, including complications and recurrence. Result: A total of 36 eyes of 35 individuals with mean age 46.51±16.44 (range: 10-84) years were included. Male predilection (63%) was observed. Unilateral presentation was seen in 97% and bilateral involvement in one case with Xeroderma Pigmentosa. Nasal bulbar conjunctiva was involved in 25 out of 36 eyes (69.4%). All 36 eyes were treated with surgical excision followed by histopathological examination. All patients were followed up for two years. Conjunctival intraepithelial neoplasia (CIN) III was the most common finding histologically, with 11 (30.5%) patients, followed by benign lesions in 10 (27.8%) patients. Six patients had CIN II, with the lowest number of cases. Surgical margins were involved in 10 (27.8%) patients who underwent further adjuvant chemotherapy with topical Mitomycin-C (MMC). Only one (2.8%) out of 36 eyes had recurrence. Post-operative complications were seen in two (5.6%) cases. Thin sclera was observed in one case, and punctal stenosis occurred in one case that received MMC post-operatively. Conclusion: In current study, the demographic profile showed OSSN being more common in the middle age group with male predilection. The overall prognosis of surgical management of OSSN with margin clearance is fairly good, with a low recurrence rate and adverse effects.